Evaluation of nursing team's knowledge in the use of dental instrumentation under general anesthesia in caring for individuals with disabilities: A pre and post-training analysis (Research, Society and Development, 2023)
Objective: To assess the knowledge of the Nursing team in a pediatric hospital regarding dental instrumentation under general anesthesia in the care of individuals with disabilities before and after a training session. Method: Data was collected through a questionnaire, answered before and after the training session, containing the same questions that cover the objectives of this research. After the questionnaire administration, a theoretical training session was conducted, with a total duration of 10 hours, followed by a reapplication of the test. To compare the results of the assessments between the pre- and post-training groups, Analysis of Variance (ANOVA) with Tukey's post hoc test (mean comparison) was performed using GraphPad Prism 8 software. The significance level was set at 95% (p < 0.05). Results: Twenty professionals participated in this study. A knowledge level of 30.80% regarding instrumentation was observed before the training, which increased to 73.30% after the training. Conclusions: This study conducted to train and enhance professionals' knowledge regarding dental instrumentation in a hospital setting was of utmost importance and brings significant benefits to the quality and effectiveness of hospital dental care.